Role of instability in the cis action of the insertion sequence IS903 transposase. - Derbyshire, K M (1990)
An unusual subset of DNA-binding proteins, termed cis-acting proteins, has been shown to act preferentially at their site of synthesis; the transposases of several bacterial insertion sequences (ISs) fall into this class. The transposase of IS903 exhibits a strong preference for action in cis: complementation of defective transposons in trans occurs at less than 1%. Furthermore, transposition mediated by transposase acting in cis is extremely sensitive to the distance between the 3' end of the transposase gene and the nearest transposon inverted repeat; we find that an insertion of 1 kilobase of DNA reduces transposition to 1-2% of control levels. Here we show that there is a strong correlation between the stability of transposase and its ability to act in trans. We found that the wild-type transposase is a very unstable protein with a physical half-life of about 3 min. However, a transposase-beta-galactosidase fusion protein has a much greater half-life and can act equally well in cis or in trans. In addition, the native transposase is stabilized in lon- strains of Escherichia coli, and, in these protease-deficient strains, trans action of transposase is increased 10- to 100-fold. These results suggest that instability of the IS903 transposase is a major determinant of its cis action and that the La protease, product of the lon gene, is an important determinant of transposase instability.